The Role of Environmental Education in Promoting Healthy Behaviors Among Primary School Students - Zuhriyah Zuhriyah (Inspire Global Insight Journal, 2026)
Purpose of the study: Environmental health challenges in developing countries significantly impact children's wellbeing, with primary school students being particularly vulnerable to poor hygiene practices and environmental health risks. Environmental education has emerged as a promising intervention strategy to promote healthy behaviors among young learners. This study aimed to evaluate the effectiveness of a comprehensive environmental education program in improving health-related knowledge, attitudes, and behaviors among primary school students in North Sumatra, Indonesia. Materials and methods: A quasi-experimental pre-test and post-test control group design was employed with 240 students aged 9-11 years from four public primary schools in Kecamatan Perbaungan, Sumatera Utara. The experimental group (n=120) received a 10-week environmental education module integrated into the science curriculum, while the control group (n=120) received standard curriculum instruction. The intervention comprised four components: personal hygiene education, waste management training, clean water and sanitation awareness, and healthy diet promotion. Data were collected using knowledge assessments, behavioral observation checklists, and attitude scales. Results: Significant improvements were observed in the experimental group compared to the control group. Post-intervention knowledge scores increased from 12.3±2.1 to 19.8±1.9 (p<0.001). Positive behavioral changes were documented in handwashing practices (85% vs. 34%), proper waste disposal (78% vs. 41%), and healthy food choices (72% vs. 38%). Attitude scores toward environmental health behaviors improved significantly (4.2±0.6 vs. 2.8±0.7, p<0.001). Conclusions: Environmental education significantly enhances health-related knowledge, attitudes, and behaviors among primary school students. Integration of environmental health education into school curricula represents an effective strategy for promoting sustainable healthy behaviors in young populations.